Keragaan Hasil dan Keuntungan Usahatani Padi dengan Introduksi Varietas Unggul di Provinsi Banten - Resmayeti Purba; Yuti Giametri (Jurnal Ilmu Pertanian Indonesia, 2017)
The adoption of a new varieties of rice (VUB) are expected could increase the rice production. The study carried out in District of Serang, Pandeglang, Lebak, and Serang City, where each location is implemented in seven villages, so there are 28 locations. The Study of VUB was held on two cropping seasons, that is cropping season II on 2013 and cropping season I on 2014. The new varieties of rice were introduced is Inpari-13, Inpari-15, Inpari-18, and Inpari-19. Rice yields productivity Inpari-19 7.2 ton/ha, is higher than Inpari-13 (6.62 ton/ha), Inpari-15 (6.69 ton/ha), Inpari-18 (6.59 ton/ha), Ciherang (6,30 ton/ha), and Mekongga (6.4 ton/ha). Based on the technical aspects, shows that Inpari-19 adaptive and can increase the yield productivity of 900 kg/ha compared to Ciherang 800 kg/ha, and Mekongga. From the economical aspect the advantages of farming using Inpari-19 and based on the social aspect, showing that the preference of farmers to Inpari-19 like more than Inpari-13, Inpari-15, and Inpari-18. Based on the technical aspects, economic and social, the Inpari-19 can be used as an alternative choice of lowland rice varieties.